Efektivitas Pemberian MP-ASI Berbasis Kearifan Lokal Terhadap Peningkatan Berat Badan Balita Gizi Kurang Di Wilayah Puskesmas Duren Sawit Tahun 2025 - Marina Marina; Nur Siti Yaroh; Tuty Yanuarti (Indonesian Journal of Innovation Science and Knowledge, 2026)
Complementary feeding (CF) refers to additional foods or beverages containing essential nutrients that are introduced to infants aged 6–24 months to complement breast milk and meet their nutritional requirements. After the age of six months, infants' nutritional needs increase in line with their growth and development, while breast milk production gradually declines. Therefore, infants require complementary foods to fulfill their nutritional needs. This study was conducted in December 2025. The sample consisted of 30 under-five children in the working area of Duren Sawit Community Health Center, selected using a purposive samplingtechnique. The results showed that before the intervention, the mean body weight was 9.3000 kg with a standard deviation of 1.80325. After the intervention, the mean body weight increased to 9.5667 kg with a standard deviation of 1.81342, indicating an average weight gain of approximately 300 grams. The findings demonstrated that local wisdom-based complementary feeding was effective in increasing the body weight of undernourished children under five in the working area of Duren Sawit Community Health Center. It is recommended that parents improve their knowledge of local wisdom-based complementary feeding through both formal and informal educational activities, including health counseling programs, so that mothers are better equipped to prepare nutritious meals thatmeet their children's nutritional needs according to their developmental stage.